2011
DOI: 10.4137/cment.s6769
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surgery in Isolated Concha Bullosa

Abstract: Objective:To study the benefit of surgery in different types of isolated concha bullosa.Design:Prospective case series.Setting:Academic Medical Center.Patients:Forty seven symptomatic patients complaining of nasal congestion and block, headache and facial pain having concha bullosa without any other sinonasal finding. Their conchae bullosa were classified as lamellar, bulbous and extensive concha bullosa. They were subjected to endoscopic operation.Main outcome measures:Subjective evaluation of postoperative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
2
9
1
Order By: Relevance
“…One of the most common anatomical sinonasal variations is middle turbinate concha bullosa, which can be small or large, unilateral or bilateral, and unichambered or multichambered . Concha bullosa has been thought to cause headache or facial pain even in the absence of mucosal contact . However, our results, as well as those in other studies, showed no significant relationship between concha bullosa and headache …”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…One of the most common anatomical sinonasal variations is middle turbinate concha bullosa, which can be small or large, unilateral or bilateral, and unichambered or multichambered . Concha bullosa has been thought to cause headache or facial pain even in the absence of mucosal contact . However, our results, as well as those in other studies, showed no significant relationship between concha bullosa and headache …”
Section: Discussioncontrasting
confidence: 61%
“…3 Concha bullosa has been thought to cause headache or facial pain even in the absence of mucosal contact. [50][51][52] However, our results, as well as those in other studies, showed no significant relationship between concha bullosa and headache. 43 Certain types of excessive pneumatization of PNSs are thought to cause headaches.…”
Section: Discussionsupporting
confidence: 50%
“…This has been supported by significant statistical correlation that has been observed between the results of tubal manometric measurements for Eustachian dysfunction and increased nasal resistance by rhinomanometric and constant body plethysmography (Jaeger), respectively, in two separate studies. [5,6] Different techniques for turbinoplasty include endoscopic partial lateral middle turbinectomy [7] and evacuation conchoplasty [8] for surgical management of concha bullosa. We used the latter technique in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Badran et al 2011 36 studied 47 patient sinuses CT scan showing pneumatisation of middle turbinate and found 17% cases of lamellar, 46.8% cases of bullous and 36.2% cases of extensive concha bullosa.…”
Section: Severity Of Concha Bullosa On Ct Imaging -mentioning
confidence: 98%